3D macro-element modelling approach for seismic assessment of historical masonry churches. (July 2016) - Pantò, B.; Cannizzaro, F.; Caddemi, S.; Caliò, I.
Highlights: A macro-element to simulate the in- and out-of-plane response of masonry structures is proposed. The approach is based on a three-dimensional discrete element and requires a low computational cost. The performance is assessed by means of nonlinear static analyses on a historical masonry church. Abstract: Recent earthquakes have demonstrated the high vulnerability of cultural heritage buildings, whose seismic assessment and rehabilitation constitute an important issue in seismic regions around the world. The high nonlinear behaviour of masonry material requires ad hoc refined finite element numerical models, whose complexity and computational cost are generally unsuitable for practical applications. For these reasons many authors proposed simplified numerical strategies to be used in engineering practice. However, most of these alternative methods are oversimplified since based on the assumption of in plane behaviour of masonry walls. In this paper a discrete-modelling approach for the simulation of both the in plane and out of-plane response of masonry structures is proposed. The method is applied to a basilica plan church, which has been partially investigated in the literature. The results show the capability of the proposed discrete element approach to simulate the nonlinear response of monumental structures also in those cases in which the 'in' and the 'out' of plane response cannot be decoupled, as it happens for many structural layouts typical of churches, ancient palaces and several other monumental structures.